2015
DOI: 10.1111/ctr.12672
|View full text |Cite
|
Sign up to set email alerts
|

Peak oxygen uptake and self‐reported physical health are strong predictors of long‐term survival after heart transplantation

Abstract: Background Peak oxygen uptake (VO2peak) is known as the gold standard measure of cardiopulmonary fitness. We therefore hypothesized that measures of physical health would predict long‐term survival in heart transplant recipients (HTx). Methods This retrospective study investigated survival in two HTx populations; the cardiopulmonary exercise test (CPET) cohort comprised 178 HTx patients who completed a VO2peak test during their annual follow‐up (1990–2003), and the SF‐36 cohort comprised 133 patients who compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 80 publications
4
44
0
3
Order By: Relevance
“…Furthermore, the study population had an aerobic performance with a mean VO 2peak of 75% of expected age‐matched values, which is above the normal range described after HTx . These results are likely to be relevant to overall prognosis, as recent studies have demonstrated an important association between cardiac rehabilitation, physical capacity, and self‐reported physical health on long‐term survival in HTx recipients …”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Furthermore, the study population had an aerobic performance with a mean VO 2peak of 75% of expected age‐matched values, which is above the normal range described after HTx . These results are likely to be relevant to overall prognosis, as recent studies have demonstrated an important association between cardiac rehabilitation, physical capacity, and self‐reported physical health on long‐term survival in HTx recipients …”
Section: Discussionmentioning
confidence: 72%
“…Several studies have demonstrated that regular exercise training improves exercise capacity and peak oxygen uptake (VO 2peak ) in heart transplant (HTx) patients, but their capacity still remains subnormal compared with the age‐matched values in a general population . Because both reduced physical exercise capacity and self‐reported physical health appear to be associated with reduced survival, an exercise training program following a transplantation should be of high importance. This is strongly supported in patients with heart failure and cardiovascular disease…”
Section: Introductionmentioning
confidence: 99%
“…Уровень пикового VO 2 , равный 10,3 (9,(4)(5)(6)(7)(8)(9)(10)(11)6) мл/мин/кг и VE/VCO 2 slope, равный 42 (35-46), полу-ченные в нашем исследовании, свидетельствуют о плохом прогнозе заболевания и являются показа-нием для трансплантации сердца [11].…”
Section: Discussionunclassified
“…Уро-вень качества жизни не только позволяет оценить субъективное восприятие пациентом эффективности проведенного лечения и возможности адаптации в социальной среде после операции, но и сам по себе имеет высокую предикторную ценность в отношении долгосрочной выживаемости [6,7]. Предполагается, что повышение толерантности к физической нагрузке после трансплантации сердца должно сопровож-даться повышением качества жизни.…”
unclassified
“…[2][3][4] Peak oxygen uptake ( _ VO 2peak ), 5 end-tidal gas tensions, 6 and oscillatory breathing 7,8 measured by cardiopulmonary exercise testing (CPET) are prognostic of mortality in HF, and _ VO 2peak and lactate threshold (LT) are used for risk stratification, such as to guide suitability for transplant. 4,[9][10][11] The relationship between ventilation ( _ V E ) and carbon dioxide output ( _ VCO 2 ) (either as the _ V E = _ VCO 2 slope, or the value of _ V E = _ VCO 2 at a specified submaximal metabolic rate; eg, at LT or the ventilatory compensation point [VCP]), typically provides one of the strongest prognosticators, [12][13][14] either independently or in combination with other CPET and non-CPET variables. 15,16 Recently, the ratios of pulmonary gas exchange to ventilation ( _ VO 2 = _ V E and _ VCO 2 = _ V E , termed circulatory equivalents) have been added to the list of CPET-derived variables.…”
mentioning
confidence: 99%